2011
DOI: 10.1186/1752-0509-5-111
|View full text |Cite
|
Sign up to set email alerts
|

Negative auto-regulation increases the input dynamic-range of the arabinose system of Escherichia coli

Abstract: BackgroundGene regulation networks are made of recurring regulatory patterns, called network motifs. One of the most common network motifs is negative auto-regulation, in which a transcription factor represses its own production. Negative auto-regulation has several potential functions: it can shorten the response time (time to reach halfway to steady-state), stabilize expression against noise, and linearize the gene's input-output response curve. This latter function of negative auto-regulation, which increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 49 publications
7
92
0
Order By: Relevance
“…S6B). Both of these roles are consistent with previous analysis of negative feedback loops (37)(38)(39).…”
Section: Mathematical Modeling Shows That the Stressosome Can Enablesupporting
confidence: 81%
“…S6B). Both of these roles are consistent with previous analysis of negative feedback loops (37)(38)(39).…”
Section: Mathematical Modeling Shows That the Stressosome Can Enablesupporting
confidence: 81%
“…To introduce negative feedback, we assume that binding of pSub to either form of the kinase causes its reversible inactivation. We observe a more graded response as a function of the signal in the presence of negative feedback, as has been reported for some other biochemical networks (35)(36)(37), while the threshold value is unchanged (Fig. 1D).…”
Section: Loss Of Negative Feedback Can Eradicate Information Transfer Bysupporting
confidence: 65%
“…The AraC TF regulates the ara operon [1,14,18,20,26,52,54,59].Recent studies have shown that araCand the ara operon share a common regulatory protein,cAMP Receptor Protein (CRP),which is activated by cAMP. AraC both activates and represses the ara operonusing a DNA looping mechanism.…”
Section: The L-arabinose Operonmentioning
confidence: 99%
“…In an NAR motif, a transcription factor (TF) negatively regulates the promoter of its own gene or operon. This has been found to 1. dramatically increase response acceleration and 2. increase the stability of the gene product concentration response to noise [26,41].…”
Section: The L-arabinose Operonmentioning
confidence: 99%
See 1 more Smart Citation